2010
DOI: 10.1111/j.1540-8167.2009.01668.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cryoballoon Technique for Mapping and Isolating Pulmonary Veins: A Feasibility and Efficacy Study

Abstract: The use of a cryoballoon catheter equipped with a 6-pole micromapping catheter inserted through its central lumen for the purpose of mapping and ablation during PV isolation procedures is both feasible and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 15 publications
1
41
1
Order By: Relevance
“…Initially the catheter tip irrigation allowed to perform more extensive lesions; more recently these catheters have been strengthened with the assistance of contact-force-sensing technology to ensure a real-time, objective measure of contact force between the catheter tip and the beating heart wall during ablation. Furthermore, durability of lesion can be ameliorated by the utilization of new ablation catheter configurations, for example balloon catheters, or by the utilization of alternative sources of energy, such as cryothermal and laser energies [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Initially the catheter tip irrigation allowed to perform more extensive lesions; more recently these catheters have been strengthened with the assistance of contact-force-sensing technology to ensure a real-time, objective measure of contact force between the catheter tip and the beating heart wall during ablation. Furthermore, durability of lesion can be ameliorated by the utilization of new ablation catheter configurations, for example balloon catheters, or by the utilization of alternative sources of energy, such as cryothermal and laser energies [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The refrigerant N 2 O is delivered into the inner balloon where it undergoes a liquidto-gas phase change, resulting in an inner balloon cooling temperature of approximately -80°C. The catheter has a central lumina, which is used for different purposes such as the insertion of the guide wire, the injection of contrast medium (diluted 1:1 ratio with 0.9% saline) for PV angiograms and eventually the insertion of a circular mapping catheter to evaluate PV isolation during cryothermal energy application [18]. Navigation of the balloon inside the LA is simplified using the 'over-the-wire' technique in conjunction with the steerable sheath (12 F, FlexCath, Medtronic Cryocath TM , USA).…”
Section: Cryoballoon Cathetermentioning
confidence: 99%
“…Prior to the recent STOP-AF trial, PV stenosis was thought to be non-existent after CBA. While multiple studies employing the use of systematic screening reported no PV stenosis (0/550 patients), the landmark STOP-AF trial noted a 3.07% (7/228 patients) incidence of radiographic PV stenosis [14,25-3214,25-32]. It is most likely that this incongruity reflects differences in criteria to define significant PV stenosis.…”
Section: Safety Of Cryoballoon Ablationmentioning
confidence: 99%
“…[14] As such, this more liberal definition may represent a relative overestimate of the rate of PV stenosis and limits direct comparisons to other studies. Even so, when the results of STOP-AF were combined with other studies employing systematic screening with non-invasive imaging, the incidence of radiographic PV stenosis was 0.90% (7/773 procedures), which is approximately half the rate observed in a large meta-analysis of conventional AF ablation with RF [7,25,32]. Reassuringly, the rate of symptomatic PV stenosis or PV stenosis requiring intervention was low (0.17%) and comparable to that observed with RF (0.1-0.3%) [7,9,10].…”
Section: Safety Of Cryoballoon Ablationmentioning
confidence: 99%